2014
DOI: 10.1139/apnm-2014-0109
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral isometric muscle fatigue decreases force production and activation of contralateral knee extensors but not elbow flexors

Abstract: Nonlocal muscle fatigue occurs when fatiguing 1 muscle alters performance of another rested muscle. The purpose of the study was to investigate if fatiguing 2 separate muscles would affect the same rested muscle, and if fatiguing the same muscle would affect 2 separate muscles. Twenty-one trained males participated in 2 studies (n = 11; n = 10). Subjects performed 2 pre-test maximum voluntary contractions (MVCs) with the nondominant knee extensors. Thereafter they performed two 100-s MVCs with their dominant k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 34 publications
2
69
2
Order By: Relevance
“…It can be concluded that the lack of changes in non-fatigued force, F100 and stability parameters contributed to the lack of change in non-dominant postural sway parameters. A briefer fatigue duration than that in a previously published similar study (Paillard et al 2010) or the use of submaximal intensity contractions as compared to MVIC (Rattey et al 2006;Martin and Rattey 2007;Halperin et al 2014a) may have contributed to the lack of crossover fatigue effects.…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…It can be concluded that the lack of changes in non-fatigued force, F100 and stability parameters contributed to the lack of change in non-dominant postural sway parameters. A briefer fatigue duration than that in a previously published similar study (Paillard et al 2010) or the use of submaximal intensity contractions as compared to MVIC (Rattey et al 2006;Martin and Rattey 2007;Halperin et al 2014a) may have contributed to the lack of crossover fatigue effects.…”
Section: Resultsmentioning
confidence: 81%
“…While Rattey et al (2006) found a decrease in voluntary activation (interpolated twitch technique) and EMG of the contralateral limb but a non-significant MVIC decrease, Martin and Rattey (2007) The sway parameters (mean ± SD) calculated during the single limb standing on the fatigued and the non-fatigued limb pre-and postfatigue * Significant difference (p < 0.05) for fatigued leg pre-versus post-fatigue ** Significant difference (p < 0.05) for non-fatigued leg pre-vs. post-fatigue # The variables which were not normally distributed and analyzed using Wilcoxon rank test. The test revealed no significant results and Halperin et al (2014a) found significant reductions in both force and EMG activity in the contralateral limb. One possible reason for the lack of agreement between Rattey et al's (2006) and Halperin et al's (2014a) works and the present research may be related to the intensity of the fatiguing contraction.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations